Identifikasi Morfologis Jenis-jenis Tumbuhan Edible di Gunung Muria Provinsi Jawa Tengah - Eri Sulis Hardianto; Rusmadi Rusmadi; Baiq Farhatul Wahidah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Mountains are one of the places that are rich in biodiversity, both flora and fauna. There are many types of plants in the mountains with various benefits, some are used as medicinal ingredients or for consumption. Mount Muria is located in the northern region of the eastern part of Central Java Province with an altitude of 1,602 meters above sea level. Knowledge of edible plants is very important to survive in the event of an emergency in the mountains. The purpose of this study was to determine the types of plants that can be consumed and the utilization of plant organs that can be consumed. This type of research is qualitative research, with data collection techniques carried out by roaming (tracking), observation, documentation, and interviews. The collected data was then analyzed descriptively. The results showed that, there were 33 species from 23 families of plants that could be consumed. The plants that can be consumed consist of fruit (57%), leaves (35%), and tubers (8%).